"Out of time": A temporal view on identity change in trailing spouses. (November 2019) - Slobodin, Ortal
Previous research on expatriate families has often emphasized the negative impact of relocation on female trailing spouses' well-being. In contrast to male employees who are sheltered from identity discontinuity by institutional frameworks, female trailing spouses often face a sudden loss of essential social and psychological functions that establish identities, such as a sense of belonging, professional achievement, and social interactions. This phenomenological study seeks to add to the discussions about the trailing spouse phenomenon by applying the role of time experience to the understanding of identity disruption and reconstruction. Although global mobility, migration, and cultural integration encompass dynamic changes in time experience, time and temporality are seldom used as central frameworks to understand how identities are transformed in the course of cultural change. Therefore, focusing on the time aspect in trailing spouses' narratives may provide insight into identity loss and construction processes. This study included in-depth interviews with 12 trailing mothers (ages 27–42 years) who relocated to the Netherlands or the United States for a limited time period to support their husband's career. Interviews were performed face to face or by video-chat and the data were analyzed using interpretative phenomenological analysis. Narratives indicated that the experience of time was a significant power in shaping trailing mothers' emotions, motivations, and behaviors during the relocation period. Specifically, three independent, interrelated attitudes toward time emerged: increased awareness of time constraints, diminished sense of time, and permanent temporariness. Taken together, these attitudes represent a failure to mourn the loss of important psychological and social aspects that once structured their lives. A failure to acknowledge this loss may limit the trailing spouses' ability to reconstruct identities in their new home and to engage in meaningful social and professional networks.